8 - Models of Economic Growth and Development in the Context of Human Capital Investment: The Way Forward for Africa - Keita, Lansana (Africa Development, 2018)
The economic literature ever since the dawn of modern economics has been much preoccupied with the issue of economic growth. Economic growth has also been understood to establish the conditions for economic development. The better-known models of economic growth such as the Lewis, Rostow, Harrod-Domar, Solow, and Romer growth models are discussed. The discussions apply contextually to the problematic issue of growth and development in Africa. It is argued that a very necessary condition for growth and transformational development in Africa is heavy investment in human capital. It is pointed out that countries that invest much human capital to produce highly educated populaces usually reap the benefits of such in terms of high per capita GDPs, regardless of the levels of their technological and industrial output. Countries like New Zealand, Iceland, and Denmark offer evidence of this. Models of African development such as the Lagos Plan of Action in terms of the whole continent are discussed within the context of existing impediments to such progress.